An investigation into the linguistic features of moderators’ language in economic forum - Võ Thị Trà My (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This study focuses on finding out the linguistic features of moderators‘ language in Economic Forum. A descriptive study was conducted based on the qualitative method. With 100 samples collected from Economic Forum in form of electronic texts as transcripts on the internet, the study attempts to find out some typical features in terms of linguistic features and discourse functions to suggest some implications for teaching English to Vietnamese learners. The findings obtained show that the move types of moderators‘ language include Initiating Move and Embedded Acts, Focusing on the Topics, Introducing Speakers, Activating Question and Answer, and Ending/Closing the Panel. Regarding syntactic features, some structures were found to be used for the realizations of the speech acts and moves, namely Declarative sentence, Interrogative sentence, Exclamative sentence, Imperative sentence, and especially Minor Clause and Elliptical Clause. These linguistic structures were found to signal the moves and illocutionary acts to attract the listeners‘ attentions and to fulfill the tasks of a moderator‘s role in economic forums. With regard to the qualitative results of speech act analysis, some pragmatic features of Moderators‘ Language such as Representatives, Expressives, Directives, and Declaration were identified as the speech acts of a transaction assumed by a moderator. It is hoped that the results of the research will serve as an access to a profound understanding of moderators‘ language in Economic forum. Furthermore, the study is expected to be recognized as a contribution to the practice of English teaching and learning.